Extracellular RNA as a kind of communication molecule and emerging cancer biomarker - Wu, Danny; Tao, Tao; Eshraghian, Emily A.; Lin, Peixu; Li, Zesong; Zhu, Xiao (Frontiers in Oncology, 2022)
Extracellular RNA (exRNA) is a special form of RNA in the body. RNA carries information about genes and metabolic regulation in the body, which can reflect the real-time status of cells. This characteristic renders it a biomarker for disease diagnosis, treatment and prognosis. ExRNA is transported through extracellular vesicles as an information molecule to mediate communication between cells. Tumor cells can release more vesicles than normal cells, thereby promoting tumor development. Depending on its easy detection, the advantages of non-invasive molecular diagnostic technology can be realized. ExRNA has considerable potential as a biomarker for tumor diagnosis, treatment and prognosis. In this systematic review, we present the types, vectors, and biological value of exRNA. We briefly describe new methods of tumor diagnosis and treatment, as well as the difficulties faced in the progress of such research. This review highlights the groundbreaking potential of exRNA as a clinical biomarker.